Consistency of the “central vein sign” in chronic multiple sclerosis lesions - Reichl, Matthias; Wittayer, Matthias Sebastian; Weber, Claudia Ellen; Platten, Michael; Gass, Achim; Eisele, Philipp (Multiple Sclerosis and Related Disorders, 2022)
Background - In recent years, there has been an increasing interest in the central vein sign (CVS) as a new imaging marker and previous cross-sectional studies demonstrated that the CVS has the potential to discriminate multiple sclerosis (MS) lesions from non-MS lesions. The aim of this study was to investigate the consistency of the CVS in a longitudinal magnetic resonance imaging (MRI) data set. - Methods - 3T MRI datasets from seventy-one people with MS acquired at baseline and after 12 months-follow-up were analyzed. Chronic lesions were identified on fluid-attenuated inversion recovery (FLAIR) images. Co-registered susceptibility-weighted/FLAIR images were analyzed for the presence of a CVS at baseline and follow-up. - Results - A total of 183 chronic lesions were included in the final analysis. At baseline MRI, a CVS was detectable in 141/183 (77%) lesions. Overall, the CVS was consistent in 114/141 (81%) lesions (Cohen's kappa = 0.46, standard error = 0.07). - Conclusion - The CVS is a rather stable feature in chronic MS lesions and therefore represents a robust imaging marker that could increase the specificity of MRI in MS.
Online verfügbar: 15. Januar 2022, Artikelversion: 21. Januar 2022
Im Titel ist “central vein sign” in Anführungszeichen geschrieben
Gesehen am 14.05.2024